2019
DOI: 10.1080/2090598x.2019.1614243
|View full text |Cite
|
Sign up to set email alerts
|

Indications for stent omission after ureteroscopic lithotripsy defined: A single-institution experience with cost analysis

Abstract: Objectives: To report on our experience with the use of an evidence-based algorithm defining specific indications for stent omission (SO) after ureteroscopic lithotripsy (URSL), as stent placement has been associated with increased cost and morbidity and indications for SO in the setting of uncomplicated ureteroscopy have been proposed but remain vague. Patients and methods: Indications for SO were defined as per the attached figure, data from URSL procedures performed from January 2016 to September 2017 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The majority of scenarios appropriate for stent omission occurred in pre-stented patients; however, many pre-stented scenarios were either inappropriate or uncertain. While some may advocate for stent omission in all pre-stented uncomplicated URS, 23 this sentiment was not shared by the panel. Additionally, previous studies have demonstrated the safety of stent omission following UAS use in select pre-stented patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of scenarios appropriate for stent omission occurred in pre-stented patients; however, many pre-stented scenarios were either inappropriate or uncertain. While some may advocate for stent omission in all pre-stented uncomplicated URS, 23 this sentiment was not shared by the panel. Additionally, previous studies have demonstrated the safety of stent omission following UAS use in select pre-stented patients.…”
Section: Discussionmentioning
confidence: 99%